From the mixed-up files of Mrs. Basil E. Frankweiler - Konigsburg, E. L. (New York, NY : Dell, 1967)
Having run away with her younger brother to live in the Metropolitan Museum of Art, twelve-year-old Claudia strives to keep things in order in their new home and to become a changed person and a heroine to herself.
"A Yearling book."
Added Econoclad ISBN 8/95/sv.
Keywords: Metropolitan Museum of Art (New York, N.Y.) -- Fiction; Runaways -- Fiction; Brothers and sisters -- Fiction; Newbery Medal